BC and 1, 4NQ-BC up-regulate the cytokines and enhance IL-33 expression in LPS pretreatment of human bronchial epithelial cells☆. (15th March 2021) - Ge, Jianhong; Chu, Hongqian; Xiao, Qianqian; Hao, Weidong; Shang, Jing; Zhu, Tong; Sun, Zhaogang; Wei, Xuetao
Abstract: Black carbon (BC) reacts with different substances to form secondary pollutants called aged black carbon, which causes inflammation and lung damage. BC and aged BC may enhance IL-33 in vivo, which may be derived from macrophages. The pro-inflammatory effect of IL-33 makes it essential to determine the source of IL-33, so it guides us to explore how to alleviate lung injury. In this study, a human bronchial epithelial cell line of 16HBE cells was selected, and aged BC (1, 4-NQ coated BC and ozone oxidized BC) was used. We found that both BC and aged BC were able to up-regulate the mRNA expression of IL-1β, IL-6, and IL-8 except IL-33. However, the Mitogen-activated protein kinases (MAPKs) and Phosphatidylinositol 3-kinase (PI3K)/Protein kinase B (AKTs) pathways remained inactive. After pretreatment with Lipopolysaccharide (LPS), IL-33 mRNA expression was significantly increased in 16HBE cells and MAPKs and PI3K/AKT were activated. These results suggested that MAPKs and PI3K/AKT pathways were involved in the elevation of IL-33. Furthermore, epithelial cells are unlikely to be the source of lung inflammation caused by elevated IL-33 in BC and aged BC. Graphical abstract: Image 1 Highlights: Black carbon and aged black carbon induce inflammatory effects in human bronchial epithelial cells. BC and aged BC-induced IL-33 in HBE cells might only be up-regulated following stimuli, like LPS challenge. MAPKs and PI3K/AKTs get involved in the elevation of IL-33 in LPS-pretreated HBE cells. BC and aged BC increase IL-1β, IL-6 and IL-33 not via MAPKs or PI3K/AKTs. Epithelial cells may not be the source of IL-33 elevated in BC and aged BC-induced inflammation.